Health and safety aspects of traditional European meat products. A review. (February 2022) - Halagarda, Michał; Wójciak, Karolina M.
Abstract: Meat products constitute one of the most important groups of traditional foods. Thanks to the unique and favorable organoleptic characteristics, and high quality, they are willingly chosen by consumers. Lately, there has been a growing concern over the health aspects of these products. Therefore, the aim of this study was to analyze the nutritional value and factors affecting quality and health safety of traditional meat products on the basis of available literature. The study findings have revealed various issues with uniformity of traditional meat products. Products of the same name may differ substantially considering nutritional value. Reports also indicate that there are some discrepancies which can be attributed to product character (traditional/conventional). They mainly concern the content of moisture, protein, salt, fat, and fatty acid profile. Research suggests that traditional meat products may also be associated with some health safety issues, such as the presence of pathogens, polycyclic aromatic hydrocarbons, nitrate and nitrite residues, N-nitrosamines, biogenic amines and heavy metals. Highlights: Traditional meat product manufacturing techniques have been outlined. Nutritional value of traditional hams and sausages has been analyzed. Health aspects of traditional hams and sausages have been discussed. Factors influencing quality of traditional meat products have been presented.